Recuperación de oro por gravimetría centrífuga y flotación de los relaves provenientes de la industria minera artesanal de La Pangui – Chinapintza - Navas Jaramillo, Santiago José (2014)
Tailings from the mining sector's Pangui underwent tests using the flotation and Knelson centrifugal concentration; Likewise a combination of these two processes are performed. For flotation were experimented with various parameters, such as: grain size, collectors and a pH of 9.5 for all trials. The results show that the best recovery rates are given using a number 179 meshes ASTM and combination of aerofloat collectors 25 and 31. To the concentration by Knelson were tested several variables, such as: grain size, pressure and a speed of 60 Gs, for all trials. Moreover, tailings were concentrated under the same conditions and then performing recalculation laws. Best results occur with finer grain size corresponding to ASTM 167 with a pressure of 1 PSI. The combination of processes was done in sequence; the Knelson equipment was first used, then flotation to complete the second stage. The results show a recovery rate of 81% was reached and it is an optimal result